The society of unknowable objects : a novel - Brown, Gareth (Novelist) (William Morrow, an imprint of HarperCollins Publishers, 2025)
"The world of unknowable objects--magical items that most people have no idea possess powers--has been quiet for decades, but the three current members of a secret society have remained watchful, meeting every six months in the basement of a bookshop in London. They are pledged to protect their archive of magical items hidden away, safe from the outside world--and the world safe from them. But when Frank Simpson, the longest-standing member of the Society of Unknowable Objects, hears of a new artifact coming to light in Hong Kong, he sends Magda Sparks--author by day and newest member--to investigate. Within hours of arriving in Hong Kong, Magda is facing death and danger, confronted by a professional killer who seems to know all about unknowable objects, specifically one that was stolen from him a decade before. Magda is forced to flee, using an artifact that not even the rest of the Society knows about. Returning to London, Magda learns hers is not the only secret being kept from the other two members. And that the most pernicious secret is about the nature of the Society's mission. Her discoveries will lead her on a perilous journey, across the Atlantic to the deep south of the United States, now in pursuit of not an unknowable object, but an unknowable person: the professional killer she first faced in Hong Kong. In doing so, Magda begins to understand that there are even more in the world who are chasing these magical items, and that her own family's legacy is tied up in keeping all these secrets under wraps. Magic has always been too powerful to reveal to the world. But Magda will learn there might be something even more powerful: the truth"--